The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1099/vir.0.023853-0
|View full text |Cite
|
Sign up to set email alerts
|

Varroa destructor is an effective vector of Israeli acute paralysis virus in the honeybee, Apis mellifera

Abstract: The Israeli acute paralysis virus (IAPV) is a significant marker of honeybee colony collapse disorder (CCD). In the present work, we provide the first evidence that Varroa destructor is IAPV replication-competent and capable of vectoring IAPV in honeybees. The honeybees became infected with IAPV after exposure to Varroa mites that carried the virus. The copy number of IAPV in bees was positively correlated with the density of Varroa mites and time period of exposure to Varroa mites. Further, we showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
159
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(164 citation statements)
references
References 22 publications
(22 reference statements)
4
159
0
1
Order By: Relevance
“…This virus was first diagnosed in Israel, where it reportedly caused large scale honeybee mortality and symptoms included trembling wings and paralysis (Maori et al, 2007;Palacios et al, 2008). The detection of IAPV in Varroa mites sampled during this study is therefore of concern, especially since it was recently confirmed that Varroa mites are capable of transmitting IAPV to honeybees (Di Prisco et al, 2011). However, IAPV was only recorded during spring 2010 in two apiaries, showing a low prevalence (Table 2).…”
Section: Discussionmentioning
confidence: 76%
“…This virus was first diagnosed in Israel, where it reportedly caused large scale honeybee mortality and symptoms included trembling wings and paralysis (Maori et al, 2007;Palacios et al, 2008). The detection of IAPV in Varroa mites sampled during this study is therefore of concern, especially since it was recently confirmed that Varroa mites are capable of transmitting IAPV to honeybees (Di Prisco et al, 2011). However, IAPV was only recorded during spring 2010 in two apiaries, showing a low prevalence (Table 2).…”
Section: Discussionmentioning
confidence: 76%
“…[1] This disappearing of the bees may lead to serious consequences. Gut microflora and parasitic mites are likely to cause this phenomenon, [2] but little is known about the honeybee gut bacteria, where there might be potential pathogens. However, a well-known honeybee pathogenic bacteria (Paenibacillus larvae) that affects honeybee larvae causes a significant decrease in the honeybee population.…”
Section: Introductionmentioning
confidence: 99%
“…Thus the present study focused on the potential association of IAPV with colony weakening represented by colonies with worse health status. Worse health status indicators included presence of clear IAPV disease symptoms, such as paralysis, loss of hair or inability to fly, depopulation, kleptoparasitism of stronger neighbouring colonies, diagnosed disease potentially associated with immune depletion such as chalkbrood (Glinski & Buczek, 2003;Aronstein & Murray, 2010); and problems to control Varroa destructor -mite infestation might lead to immunosuppression (Yang & CoxFoster, 2005), which may facilitate IAPV replication, as Varroa destructor has been described as an IAPV vector (Di Prisco et al, 2011). Sanitary status data were collected from the epidemiological surveys conducted by technicians upon sampling.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Martin et al (2012) reported similar results on the Hawaiian islands with IAPV loads in the order of 10 7 GEC/bee in covert infections not associated with colony collapse, but with lower prevalences (only 3 colonies of 293 were infected with IAPV). Based on the recent description of the V. destructor mite as a transmitter of IAPV (Di Prisco et al, 2011), future studies should also determine IAPV loads in pupae and V. destructor to better understand the biology of the virus. In this study, only the effect of IAPV presence and load was considered on weakening colonies in Andalusia.…”
Section: Introductionmentioning
confidence: 99%